Statistical Analysis in Cost Measurement and Control. - Jensen, Robert E.; Thomsen, C. Torben (The Accounting Review, 1968)
Abstract The article outlines a statistical approach in cost measurement and control which can be easily implemented in practice. This approach will allow accountants to convert certain types of costs currently treated as overhead costs into traceable direct costs. The detailed cost measurements on individual inventory items provide "more information" than knowledge of only the total inventory cost. Cost accounting systems, often very elaborate cost accounting systems, are designed to detect and measure resource flows for both product and responsibility center costing. In general, however, detection and measurement costs increase as more detailed information on resource flows is desired. Accounting systems for this reason resort to collecting aggregated information. The aggregation itself may be over various types of activities, time intervals, or products. If one desires to study marginal costs, an examination of costs allocated to idle time will prove helpful. In summary, statistical cost finding is no panacea for accounting problems, it is rather a useful tool for developing information not usually found in the books.